AA meta-analysis of outdoor recreation demand studies Why do recreation values differ across the world? - Hysková, Ivana; Melichar, Jan, 1975-; Kaprová, Kateřina; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2011)
This thesis presents a meta-analysis of forest recreation studies conducted in Europe within last 15 year. It covers 17 studies conducted across 10 countries that have applied the travel cost method. The thesis first presents theoretical background of meta-analysis. Then it reviews the literature and finally, a meta-regression analysis explaining the variances in consumer surplus (CS) across studies is conducted. The results indicate that: (1) there is statistically significant difference between the CS estimates in Eastern European countries (EEC) and the estimates in Western European countries (WEC), and (2) the CS estimates in EEC are higher than the CS estimates in WEC.
Vedoucí práce: Jan Melichar
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: ekonomika a správa životního prostředí [obor dipl. práce]; diplomové práce; master's theses